Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2012)
DIRETOR DA REVISTADesembargador Federal Antonio CedenhoASSESSORWladimir RodriguesEQUIPEFrancisco Oliveira da SilvaLucia Massako Y. C. RosaMaria José F. da RochaMônica Maria Meloni SícoliRenata Bataglia GarciaSimone de Alcântara Savazzoni